An analysis of the validity of the ‘broken promises of democracy’ by Norberto Bobbio - Soto Suárez, Camilo (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
This article aims for the purpose of analyze and demonstrate the currency of two of the six broken promises of democracy proposed by the philosopher Norberto Bobbio, namely, the renewed vigour of particular interests and the elimination of invisible power. In regard of the first promise, we will show its currency at the theoretical level, through the idea of the micropolitical and the macropolitical market-place and the idea of the ‘democracy without a demos’; and at the political-practical level, through the neocorporativism and specific examples of the political partidists discipline and the representation for binding mandate. Regarding the latter, a series of distinctions of the different types of existing invisible power will be proposed, in order to fully specify the particularities of each one. Then, its validity will be demonstrated by means of concrete cases, such as the phenomenon of scandal, the existence of institutions and intelligence services, mafia groups against the State, among others.
Keywords: Broken promises; democracy; interests; secrecy; Bobbio